Effect of Papaya and Shrimp Waste Bioactivators on Household Organis Waste Composting - Wilda Trisari; Indah Nurhayati; Sugito (Industrial and Domestic Waste Management, 2026)
This study aims to evaluate the effect of papaya bioactivator (Carica papaya) and shrimp waste bioactivator on the composting process of household organic waste, as well as changes in the levels of carbon (C), nitrogen (N), phosphorus (P), potassium (K), and the C/N ratio. The study was conducted on a laboratory scale with three treatments: R1 (papaya bioactivator), R2 (shrimp waste bioactivator), and R3 (without bioactivator). The parameters observed included pH, temperature, humidity, and color on a daily basis, as well as changes in C, N, C/N ratio, P, and K levels at the beginning and end of the composting process. The results showed that the C/N ratio decreased in all treatments, while the levels of N, P, and K increased. The shrimp waste bioactivator (R2) produced the fastest composting process in 12 days and yielded the best compost quality, with the lowest C/N ratio and the highest increases in N, P, and K levels. Conversely, the treatment without bioactivator showed a slower process, with a final C/N ratio of 33.54, indicating that the compost was not yet mature. Shrimp waste bioactivators have the potential to improve the quality and efficiency of the composting process.